Punica granatum (Pomegranate) Seed Oil and Momordica charantia (Bitter Melon) Extract Affect the Lipid's Profile and Oxidative Stability of Femoral Muscles of Rats. Issue 5 (19th March 2019) - Białek, Małgorzata; Białek, Agnieszka; Lepionka, Tomasz; Paśko, Paweł; Galanty, Agnieszka; Tokarz, Andrzej; Czauderna, Marian
Abstract : Pomegranate seed oil (PSO) and bitter melon extract (BM), used in folk medicine nowadays are available as dietary supplements, but information about consequences of their simultaneous usage are still scarce. This study aims to evaluate the influence of supplementation of rats' diet with PSO separately or jointly with BM on the fatty acid (FA), cholesterol, malondialdehyde (MDA), and tocopherols concentrations in femoral muscles. Sprague‐Dawley rats ( n  = 36) are fed control diet (group C) or experimental diets supplemented only with 0.15 ml PSO/day (group G) or together with BM (group GM). After 21 weeks of supplementation, muscles are subjected to either gas (FA and cholesterol) or liquid (conjugated FA, tocopherols, and MDA) chromatographic analyses. Applied diets do not influence negatively health and welfare of animals. Conjugated linolenic acid (CLnA) isomers, predominating in PSO, are converted into ct/tc conjugated dienes (CD), with rumenic acid being the main CD, and incorporated into muscles. Supplementation of diet with PSO decreases the cholesterol and MDA contents in muscles. Influence of PSO and BM on activity of desaturases results in varied polyunsaturated FA (PUFA) content. Some PUFA may be converted into conjugated FA either exogenously or as a result of enzymatic or non‐enzymatic processes. Practical Applications : Dietary sources of conjugated linolenic acid isomer, e.g., PSO and BM, are known for their beneficial properties and thus willingly consumed world‐wide. Limited safety information of their simultaneous use is available despite their over‐consumption and may probably cause adverse effects. PSO and BM given to rats improves a lipid profile of femoral muscles, decreases cholesterol, increases polyunsaturated fatty acids and rumenic acid content, and counteracts lipid oxidation. These results may be a starting point for experiments conducted on farm animals considering their supplementation with PSO in order to possible improvement of nutritional value of their meat. After detailed surveys confirming beneficial influence of both supplements on human health and well‐being, these botanicals may be safely introduced into human diet. This study evaluates the influence of supplementation of rats' diet with pomegranate seed oil separately or jointly with bitter melon extract on fatty acid, cholesterol, malondialdehyde, and tocopherols concentrations in femoral muscles. After 21 weeks of supplementation, muscles are subjected to either gas or liquid chromatographic analyses. Supplementation of diet with pomegranate seed oil decreases cholesterol and malondialdehyde contents. Abstract : This study evaluates the influence of supplementation of rats' diet with pomegranate seed oil separately or jointly with bitter melon extract on fatty acid, cholesterol, malondialdehyde, and tocopherols concentrations in femoral muscles. After 21 weeks of supplementation, muscles are subjected to either gas or liquid chromatographic analyses. Supplementation of diet with pomegranate seed oil decreases cholesterol and malondialdehyde contents.